A model of collaboration for the implementation of problem-based learning in nursing education in South Africa - Mahlasela A. Rakhudu; Mashudu Davhana-Maselesele; Ushonatefe Useh (AOSIS, 2017)
Background: The idea of collaboration between key stakeholders in nursing education for the implementation of problem-based learning (PBL) may have far-reaching implications for the institutions and students. Main objective: To develop a model of collaboration to facilitate the implementation of PBL in nursing education. Methodology: An exploratory sequential design was used. Qualitative data were collected from purposively recruited nurse educators from three universities in South Africa offering PBL and nurse managers from all the three hospitals in North West Province where PBL students are placed for clinical learning. A questionnaire was used to obtain data from respondents who were conveniently recruited. Model development, concept analysis, construction of relationships, description and evaluation were followed. Results: This model has six elements: higher education and nursing education (context), institutions initiating PBL, clinical services, colleges affiliated to PBL universities, students and healthcare users (recipients), champions in PBL (agents), effective implementation of PBL (terminus), collaboration (process) and commitment, communication, trust and respect (dynamics). Conclusion: Collaboration in implementing PBL can be a functional reality in the delivery of quality educational experiences and has far-reaching implications for the institutions and students. The implementation of the model in South African nursing education institutions may be necessary for the light of the revision of the preregistration qualifications. Recommendations: Managerial commitment, training of collaborators on PBL and collaboration skills, memorandum of agreement, monitoring and evaluation are critical. More research is required to pilot the model and evaluate collaboration in implementing PBL at different levels of operations.